ANALYSIS OF OPERATIONAL RISK MANAGEMENT OF KAMPUNG SUSU DINASTY AGROTOURISM IN SIDEM VILLAGE GONDANG SUBDISTRICT TULUNGAGUNG REGENCY - Halimah, Azki Nur; Widayanti, Sri; Yuliati, Nuriah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Kampung Susu Dinasty (KSD) Agrotourism hasn’t managed their management optimally. This condition has an impact on agrotourism that has a hard time to developing. This management isn’t free of a risk and the possibility of a risk that’s influenced by the quality said management has. This research aims to identifying the operational risk source, analyzing the level of risk, also strategies that can be applied for operational agrotourism risk control. The research method used is qualitative descriptive. The sampling method used is purposive sampling technique with 64 respondents. Data analysis used descriptive analysis, likert scale, Godfrey method, and Flanagan & Norman theory. The result shows that there are 13 operational risks that agrotourism faces with 4 risk categories. The final results of the risk level assessment found that 2 risks were at a low level, 5 risks were at a medium level, 3 risks were at high level, and 3 risks were at an extreme level. From the results of the analysis, 4 main strategies were carried out to minimize losses due to operational risks, namely by transferring risks involving third parties, establishing communication and cooperation with various parties, creating alternative actions, and creating new programs.